2018
DOI: 10.1186/s12885-018-4629-6
|View full text |Cite
|
Sign up to set email alerts
|

Possible roles of genetic variations in chemotherapy related cardiotoxicity in pediatric acute lymphoblastic leukemia and osteosarcoma

Abstract: BackgroundThe treatment of acute lymphoblastic leukemia (ALL) and osteosarcoma (OSC) is very effective: the vast majority of patients recover and survive for decades. However, they still need to face serious adverse effects of chemotherapy. One of these is cardiotoxicity which may lead to progressive heart failure in the long term. Cardiotoxicity is contributed mainly to the use of anthracyclines and might have genetic risk factors. Our goal was to test the association between left ventricular function and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 86 publications
0
47
0
5
Order By: Relevance
“…The results of multivariate analysis showed that the incidence of congestive heart failure (CHF) was higher in patients with pre-HCT chest radiation and with gene variants coding for the NOX subunit RAC2 (rs13058338), HFE (rs1799945), or the DOX efflux transporter ATP-binding cassette subfamily C member 2 (ABCC2, rs8187710) [ 35 , 39 ]. In addition, the polymorphisms of NOX subunits and transporters ABCC1, ABCC2, and SLC28A3 were genotyped in patients with aggressive CD20 B-cell lymphoma [ 40 , 41 ]. The RAC2 subunit genotypes were found to have statistical significance in the multivariate logistic regression analysis.…”
Section: Susceptibility Genes In Chemotherapy-induced Cardiotoxicimentioning
confidence: 99%
“…The results of multivariate analysis showed that the incidence of congestive heart failure (CHF) was higher in patients with pre-HCT chest radiation and with gene variants coding for the NOX subunit RAC2 (rs13058338), HFE (rs1799945), or the DOX efflux transporter ATP-binding cassette subfamily C member 2 (ABCC2, rs8187710) [ 35 , 39 ]. In addition, the polymorphisms of NOX subunits and transporters ABCC1, ABCC2, and SLC28A3 were genotyped in patients with aggressive CD20 B-cell lymphoma [ 40 , 41 ]. The RAC2 subunit genotypes were found to have statistical significance in the multivariate logistic regression analysis.…”
Section: Susceptibility Genes In Chemotherapy-induced Cardiotoxicimentioning
confidence: 99%
“…Ko and Shin [65] demonstrated that cardio-sulfa caused aberrant heart development in zebrafish and was activated through the AhR signaling pathway in a CYP1A -independent manner. Research results indicate that variations in the ABCC2 gene might influence the left ventricular parameters [66]. Additionally, AHR is highly correlated with heart defects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been observed that SLC28A3 can transport several anthracyclines drugs including doxorubicin into cells, providing a potential mechanism by which these variants could affect ACT. Studies have provided evidence for the association among of rs7853758 (p.Leu461Leu) and rs885004 (Leu248Leu) with ACT [ 40 , 44 ]. The most consistent results were found between the minor allele rs7853758 461Leu with ACT [44] , [45] , [46] , which is also associated and with reduced SLC28A3 mRNA expression in monocytes [47] .…”
Section: Germline Variants Mutations and Treatment Responsementioning
confidence: 99%
“…Studies have provided evidence for the association among of rs7853758 (p.Leu461Leu) and rs885004 (Leu248Leu) with ACT [ 40 , 44 ]. The most consistent results were found between the minor allele rs7853758 461Leu with ACT [44] , [45] , [46] , which is also associated and with reduced SLC28A3 mRNA expression in monocytes [47] . Although scarce evidences regarding the role of this SNP in ALL, there is a recommendation for genetic testing to all patients under anthracyclines treatment to reduce the incidence of ACT [ 40 , 46 ].…”
Section: Germline Variants Mutations and Treatment Responsementioning
confidence: 99%